Relationships between leaf morphological traits, nutrient concentrations and isotopic signatures for Mediterranean woody plant species and communities - Domínguez, María T.; Aponte, Cristina; Pérez-Ramos, Ignacio M.; García, Luis V.; Villar, Rafael; Marañón, Teodoro (Plant and Soil, 2012)
Background and aims Soil factors are driving forces that influence spatial distribution and functional traits of plant species. We test whether two anchor morphological traits—leaf mass per area (LMA) and leaf dry matter content (LDMC)—are significantly related to a broad range of leaf nutrient concentrations in Mediterranean woody plant species. We also explore the main environmental filters (light availability, soil moisture and soil nutrients) that determine the patterns of these functional traits in a forest stand. Methods Four morphological and 19 chemical leaf traits (macronutrients and trace elements and δ 13 C and δ 15 N signatures) were analysed in 17 woody plant species. Community-weighted leaf traits were calculated for 57 plots within the forest. Links between LMA, LDMC and other leaf traits were analysed at the species and the community level using standardised major axis (SMA) regressions Results LMA and LDMC were significantly related to many leaf nutrient concentrations, but only when using abundance-weighted values at community level. Among-traits links were much weaker for the crossspecies analysis. Nitrogen isotopic signatures were useful to understand different resource-use strategies. Community-weighted LMA and LDMC were negatively related to light availability, contrary to what was expected. Conclusion Community leaf traits have parallel shifts along the environmental factors that determine the community assembly, even though they are weakly related across individual taxa. Light availability is the main environmental factor determining this convergence of the community leaf traits.
Keywords: Community weighted means; functional traits; isotopes; leaf dry matter content; Leaf mass per area; macronutrients; Specific leaf area

Leaf morphology and macronutrients in broadleaved trees in central Italy - Bussotti, Filippo; Borghini, Francesca; Celesti, Carlo; Leonzio, Claudio; Bruschi, Piero (Trees, 2000)
As part of an intensive monitoring programme (MON.I.TO, Intensive Monitoring of Forests in Tuscany), a 3-year survey was carried out, which included three tree species (beech, Fagus sylvatica L.; Turkey oak, Quercus cerris L.; holm-oak, Quercus ilex L.) located at six different sites. Leaves were sampled annually and analysed for nutrient concentrations (nitrogen, sulphur, phosphorus, magnesium, calcium, potassium and sodium) and morphological parameters (leaf area, dry weight, leaf mass per area, leaf thickness and leaf density). Results indicated considerable interannual variation of all the parameters. Differences between sampling sites indicated that, of all parameters measured, leaf mass per area could explain best the differences in field performance under conditions of stress. In fact, leaf mass per area was greater in the drier sites or when sea salt deposition occurred. Nevertheless, the variation of leaf mass per area over the 3 years did not reflect the differences in rainfall. Higher leaf mass per area was accompanied by lower concentrations of phosphorus and nitrogen, which could be a dilution effect due to an increase of structural carbon compounds in sclerophyllous leaves, as revealed by the total foliar content of these elements. Leaf mass per area as a measure of sclerophylly reached very high values among mesophile vegetation. Long-range transport of sea salt from coastal areas to mountain areas was mirrored in sodium concentrations of leaves.
Keywords: Fagus sylvatica; macronutrients; Quercus cerris; Quercus ilex; sclerophylly

Leaf morphology and macronutrients in broadleaved trees in central Italy - Bussotti, Filippo; Borghini, Francesca; Celesti, Carlo; Leonzio, Claudio; Bruschi, Piero (Trees, 2000)
As part of an intensive monitoring programme (MON.I.TO, Intensive Monitoring of Forests in Tuscany), a 3-year survey was carried out, which included three tree species (beech, Fagus sylvatica L.; Turkey oak, Quercus cerris L.; holm-oak, Quercus ilex L.) located at six different sites. Leaves were sampled annually and analysed for nutrient concentrations (nitrogen, sulphur, phosphorus, magnesium, calcium, potassium and sodium) and morphological parameters (leaf area, dry weight, leaf mass per area, leaf thickness and leaf density). Results indicated considerable interannual variation of all the parameters. Differences between sampling sites indicated that, of all parameters measured, leaf mass per area could explain best the differences in field performance under conditions of stress. In fact, leaf mass per area was greater in the drier sites or when sea salt deposition occurred. Nevertheless, the variation of leaf mass per area over the 3 years did not reflect the differences in rainfall. Higher leaf mass per area was accompanied by lower concentrations of phosphorus and nitrogen, which could be a dilution effect due to an increase of structural carbon compounds in sclerophyllous leaves, as revealed by the total foliar content of these elements. Leaf mass per area as a measure of sclerophylly reached very high values among mesophile vegetation. Long-range transport of sea salt from coastal areas to mountain areas was mirrored in sodium concentrations of leaves.
Keywords: Fagus sylvatica; macronutrients; Quercus cerris; Quercus ilex; sclerophylly

Nutrient dynamics in crown tissues of cork-oak (Quercus suber L?.) - Oliveira, G; Martins-Loução, M a (Trees-Structure and …, 1996)
The seasonal fluctuation of N, P, K, Ca and Mg in leaves, young stems and fruits of young and mature Quercus suber trees growing at the same site was studied. Nutrient dynamics within the tree appeared to be linked to phenological events. Leaves maximized their nutrient con- tents throughout summer whereas stems maintained rather constant values during most of the year. Before the spring growth flush they apparently acted as temporary reservoirs for some nutrients, translocated from leaves or other organs, so that such nutrients would be easily invested in the new tissues. A significant investment was made in sink organs like flowers and fruits. The tree probably relies not only on leaves but also on other nutrient reservoirs like older branches and roots for an adequate supply to those sinks and to the spring growth. The importance of the sampling dates and the basis of expression used for nutrient concen- trations has also been emphasized. Nutrient contents and seasonal trends of the studied trees were similar to those of other evergreen oaks, although somewhat higher values for N, K, and Mg were found. Moreover, soil nutrient contents in the studied "montado" were much lower than in other Iberic oak stands. However the nutrient status and require- ments of cork-oak suggest high (or at least adequate) nutrient availability to the trees. The mechanisms by which this could be achieved are discussed.
Keywords: Evergreen oaks; macronutrients; montado; seasonal patterns; tissue nutrient contents

Nutrient dynamics in crown tissues of cork-oak (Quercus suber L?.) - Oliveira, G; Martins-Loução, M a (Trees-Structure and …, 1996)
The seasonal fluctuation of N, P, K, Ca and Mg in leaves, young stems and fruits of young and mature Quercus suber trees growing at the same site was studied. Nutrient dynamics within the tree appeared to be linked to phenological events. Leaves maximized their nutrient con- tents throughout summer whereas stems maintained rather constant values during most of the year. Before the spring growth flush they apparently acted as temporary reservoirs for some nutrients, translocated from leaves or other organs, so that such nutrients would be easily invested in the new tissues. A significant investment was made in sink organs like flowers and fruits. The tree probably relies not only on leaves but also on other nutrient reservoirs like older branches and roots for an adequate supply to those sinks and to the spring growth. The importance of the sampling dates and the basis of expression used for nutrient concen- trations has also been emphasized. Nutrient contents and seasonal trends of the studied trees were similar to those of other evergreen oaks, although somewhat higher values for N, K, and Mg were found. Moreover, soil nutrient contents in the studied "montado" were much lower than in other Iberic oak stands. However the nutrient status and require- ments of cork-oak suggest high (or at least adequate) nutrient availability to the trees. The mechanisms by which this could be achieved are discussed.
Keywords: Evergreen oaks; macronutrients; montado; seasonal patterns; tissue nutrient contents